Theoretical global seismology - Dahlen, F. A., 1942- (Princeton University Press, 1998)
After every major earthquake, the Earth rings like a bell for several days. These free oscillations of the Earth and the related propagating body and surface waves are routinely detected at broad-band seismographic stations around the world. In this comprehensive treatise, Dahlen and Tromp present an up-to-date and advanced theoretical treatment of global seismology, describing the normal-mode-body-wave, and surface-wave methods employed in the determination of the Earth's three-dimensional internal structure and the source mechanisms of earthquakes. As a long-needed unification of methods and results in this active research area.